Digital Transformation as an Enabler of Sustainability Management in the 5.0 Industry - Adrian Eka Darma Serang; Hilmi Wiranwata; Darman Syafei (Oikonomia : Journal of Management Economics and Accounting, 2025)
The emergence of Industry 5.0 marks a fundamental shift in industrial paradigms from technology-centric efficiency toward human-centric, sustainable, and resilient systems. In this context, digital transformation is no longer positioned merely as a tool for operational efficiency, but as a structural enabler of sustainability management. This study aims to systematically synthesize the academic literature on the role of digital transformation in enabling sustainability management within the Industry 5.0 framework. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, analyzing peer-reviewed journal articles with active DOIs related to digital transformation, sustainability management, and Industry 5.0. The findings reveal that digital transformation enables sustainability management through data integration, adaptive decision-making, transparency, and the alignment of economic, environmental, and social dimensions. However, the literature also identifies critical limitations and risks, including digital readiness gaps, ethical and technological biases, over-reliance on automation, and regulatory inconsistencies. This study concludes that the effectiveness of digital transformation as a sustainability enabler depends on the integration of technological capabilities, human-centered values, and governance structures. The study contributes by clarifying the enabling mechanisms of digital transformation and proposing a conceptual foundation for sustainable management practices in the Industry 5.0 era.